Empagliflozin influences blood viscosity and wall shear stress in subjects with type 2 diabetes mellitus compared with incretin-based therapy - Irace, Concetta; Casciaro, Francesco; Scavelli, Faustina Barbara; Oliverio, Rosa; Cutruzzolà, Antonio; Cortese, Claudio; Gnasso, Agostino (Cardiovascular diabetology, 2018)
Cardiovascular protection following empagliflozin therapy is not entirely attributable to the glucose lowering effect. Increased hematocrit might influence the shear stress that is the main force acting on the endothelium, regulating its anti-atherogenic function. We designed the study with the aim of investigating the effect of empagliflozin on blood viscosity and shear stress in the carotid arteries. A secondary endpoint was the effect of empagliflozin on carotid artery wall thickness. The study was a non-randomized, open, prospective cohort study including 35 type 2 diabetic outpatients who were offered empagliflozin or incretin-based therapy (7 liraglutide, 8 sitagliptin) in combination with insulin and metformin. Blood viscosity, shear stress and carotid wall thickness were measured at baseline and at 1 and 3 months of treatment. Blood viscosity was measured with a viscometer, and shear stress was calculated using a validated formula. Intima-media thickness (IMT) of the carotid artery was detected by ultrasound and was measured with dedicated software. Blood viscosity (4.87 ± 0.57 vs 5.32 ± 0.66 cP, p < 0.02) and shear stress significantly increased in the Empagliflozin group while no change was detected in the Control group (4.66 ± 0.56 vs 4.98 ± 0.73 cP, p = NS). IMT significantly decreased in the Empagliflozin group after 1 and 3 months (baseline: 831 ± 156, 1-month 793 ± 150, 3-month 766 ± 127 μm; p < 0.0001), while in the liraglutide group, IMT significantly decreased only after 3 months (baseline 879 ± 120; 1-month 861 ± 163; 3-month 802 ± 114 μm; p < 0.001). In the sitagliptin group, IMT remained almost unchanged (baseline 901 ± 135; 1-month 902 ± 129; 3-month 880 ± 140 μm; p = NS). This study is the first to describe a direct effect of empagliflozin on blood viscosity and wall shear stress. Furthermore, IMT was markedly reduced early on in the Empagliflozin group.